Synergic recombinant enzyme association to optimize xylo-oligosaccharides production from agricultural waste - Martins, Manoela (2020)
Xylo-oligosaccharides (XOS) are one of the classes of prebiotics obtained from lignocellulosic biomass, by hydrolysis of hemicellulose, abundant in agroindustrial residues. Several endoxylanases were studied in order to provide better conversion of the biomass to XOS. The resulting product presents multi-benefits, favoring the intestinal microbiota and maintaining the viability of probiotics in food. XOS production from sugarcane straw by action of thermostable recombinant endoxylanase of Cryptococcus flavescens, expressed in Pichia pastoris GS115 using vector pGAPZA, in synergic association with -l-arabinofuranosidase (GH 51) (Megazyme®) was optimized using a central composite rotatable design (CCRD), enabling 72.56% of xylan conversion. The main products xylobiose and xylotriose are short chain oligosaccharides preferred by probiotics. Hydrolysis of xylan from sugarcane straw using endoxylanase and -l-arabinofuranosidase has great potential for XOS production with high prebiotic activity, representing a possible sustainable way to reduce enzymatic and raw material costs.